Pengaruh Komitmen Organisasi terhadap Kinerja Karyawan: Systematic Literature Review - Liling Silviana,; Qori Titian Rahayu,; Dani Rizana, (Jurnal Publikasi Ilmu Manajemen, 2026)
Employee performance is one of the strategic components that influence organizational sustainability and competitive advantage in facing the dynamics of the business environment. Using a Systematic Literature Review (SLR) approach, this study aims to analyze the effect of organizational commitment on employee performance. Relevant and high-quality empirical research results were identified, selected, and synthesized through SLR. Data were obtained from the Scopus and Google Scholar databases based on the criteria of articles published in the last five years. Literature selection was carried out systematically through the stages of keyword determination, screening based on inclusion and exclusion criteria, and analysis of research substance. The study shows that organizational commitment significantly affects employee performance. Employees who are highly committed to the company tend to be more productive, loyal, and have better work quality. In addition, it was proven that continuous, affective, and normative commitment improves individual and overall organizational performance. These findings show the importance of management in building and maintaining organizational commitment so that employee performance continues to improve. This study is expected to provide theoretical and practical references for researchers and human resource practitioners.